2018
DOI: 10.4236/ajac.2018.94018
|View full text |Cite
|
Sign up to set email alerts
|

High Density Solvent Based Dispersive Liquid-Liquid Microextraction Technique for Simultaneous and Selective Extraction of Multiclass Pesticide Residues in Water and Sugarcane Juice Samples

Abstract: In this study, a miniaturized analytical technique based on high density solvent based dispersive liquid-liquid microextraction (HD-DLLME) was developed for extraction of trace residues of multiclass pesticides including three s-triazine herbicides, two organophosphate insecticides and two organochlorine fungicides from environmental water and sugarcane juice samples. The analytical method was validated and found to offer good linearity: R 2 ≥ 0.991; repeatability varied from 0.73% -5.28%; reproducibility vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The concern for health of society has led to strict regulation of maximum residue limit of pesticide residues in food [4]. Therefore, monitoring levels of these pesticides in food and environmental samples is imperative for health risk control and environment protection [5].…”
Section: Introductionmentioning
confidence: 99%
“…The concern for health of society has led to strict regulation of maximum residue limit of pesticide residues in food [4]. Therefore, monitoring levels of these pesticides in food and environmental samples is imperative for health risk control and environment protection [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the peaks of all the target analytes were increased with an increase in pH up to 5 and then lowered at higher pH values (Figure 4). This effect may be explained by the fact that the stability of the target analytes is better enhanced in weakly acidic and weakly alkaline solutions over strongly acidic and strongly alkaline solutions, where they could readily be ionized [3]. Thus, pH 5 was selected as the optimum value for the subsequent experiments.…”
Section: Effect Of the Sample Phmentioning
confidence: 99%
“…They are manufactured from multiple molecule substances obtained from various chemical groups that share some characteristics [1]. Out of the total amount of pesticides sprayed on the plants, only less than 0.1% of the applied pesticides actually reach the targeted pests; the remainder may end up on other environmental compartments and consumables like fruits and vegetables [2][3][4][5]. This has led to the need for discovery of these compounds in food, soil, and water, possibly compromising both human life and health of all other living species [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main prerequisite is the miscibility of the disperser solvent with the extraction of the organic phase [18]. As a result, three organic solvents (methanol, ethanol, and acetone) were studied as dispersants.…”
Section: Selection Of Dispersing Solventmentioning
confidence: 99%